Variations in the hysteretic behavior of LRBs as a function of applied loading - Ozdemir, Gokhan; Bayhan, Beyhan; Gulkan, Polat (Techno-Press, 2018)
The study presented herein focused on the change in hysteretic force-deformation behavior of lead rubber bearings (LRBs). The material model used to idealize response of LRBs under cyclic motion is capable of representing the gradual attrition in strength of isolator unit on account of lead core heating. To identify the effect of loading history on the hysteretic response of LRBs, a typical isolator unit is subjected to cyclic motions with different velocity, amplitude and number of cycles. Furthermore, performance of an LRB isolated single degree of freedom system is studied under different seismic input levels. Finally, the significance of lead core heating effect on LRBs is discussed by considering the current design approach for base isolated structures. Results of this study show that the response of an LRB is governed strongly by the amplitude and number of cycles of the motion and the considered seismicity level.
Keywords: lead rubber bearing; isolator tests; quality control tests; seismic isolation; lead core heating